ChemInform Abstract: Enantioselective Direct Functionalization of Indoles by Pd/Sulfoxide‐Phosphine‐Catalyzed N‐Allylic Alkylation. Issue 30 (July 2015) - Chen, Li‐Yan; Yu, Xiao‐Ye; Chen, Jia‐Rong; Feng, Bin; Zhang, Hong; Qi, Ying‐Hua; Xiao, Wen‐Jing
Abstract An efficient and scalable N‐allylic alkylation of variously substituted indole derivatives and other N‐heterocycles using diaryl and aryl alkyl propenylacetates is described which generally proceeds with high yields and enantioselectivities.